2019
DOI: 10.3390/s19030708
|View full text |Cite
|
Sign up to set email alerts
|

Technological Ecosystems in Care and Assistance: A Systematic Literature Review

Abstract: Applying the concepts of technological ecosystems to the care and assistance domain is an emerging field that has gained interest during the last years, as they allow to describe the complex relationships between actors in a technologically boosted care domain. In that context, this paper presents a systematic review and mapping of the literature to identify, analyse and classify the published research carried out to provide care and assistance services under a technological ecosystems’ perspective. Thirty-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…It consists in the fulfillment of a Business Model Canvas (BMC) that describes the interrelation of nine components of a business model. The proposed BMC is based in a literature review aimed to identify how technological ecosystem proposals address the business component [7], along with a systematic mapping study of the most relevant EU funded projects related to the health domain. The outcomes of these reviews (trends, lacks and opportunities, involved actors etc.)…”
Section: Health Ecosystem For Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists in the fulfillment of a Business Model Canvas (BMC) that describes the interrelation of nine components of a business model. The proposed BMC is based in a literature review aimed to identify how technological ecosystem proposals address the business component [7], along with a systematic mapping study of the most relevant EU funded projects related to the health domain. The outcomes of these reviews (trends, lacks and opportunities, involved actors etc.)…”
Section: Health Ecosystem For Caregiversmentioning
confidence: 99%
“…This means that they are usually discontinued despite their great potential. For example, a recent study [7], which analyzed 37 papers focused on platforms providing care and assistance services under a technological ecosystems' perspective, showed that just three papers (8%) described an ecosystem that was deployed and tested with real users under real world conditions (out of the lab). This may be because the vast majority of such proposals do not take into account the concept of value co-creation within the ecosystem, and lack a business perspective when defining the relevant data to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current proposed or developed technological health ecosystems tend to have problems when it comes to being deployed in the real world. This means that they are usually discontinued despite their great potential [4]. This may be because the vast majority of such proposals do not take into account the concept of value co-creation within the ecosystem, and lack from a business perspective when defining the relevant data to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported on smart city applications to support population surveillance, active ageing, healthy lifestyles, disabled people, response to emergencies, care services organization, and socialization. Conclusions: Most of the included articles were either of a descriptive and conceptual nature or in an early stage of development, which means that a major barrier for their dissemination is their lack of concreteness.Technologies 2019, 7, 58 2 of 16 mindedness; and smart living-quality of life of the individuals, namely health conditions, cultural and education facilities, housing quality, and touristic attractiveness.Although there is a significant number of systematic reviews related to healthcare provision supported by IT (e.g.,[6][7][8][9][10]), to the best of the authors' knowledge, systematic reviews of the literature related to the implementation of smart cities are scarce and address specific aspects (e.g., [11][12][13]). Since systematic evidence is required to inform smart city stakeholders and researchers about state of the art solutions, the systematic review reported by the present article aimed to identify the most relevant applications supported by smart city infrastructure with an impact in the provision of healthcare, which is a relevant component of smart living.…”
mentioning
confidence: 99%
“…Although there is a significant number of systematic reviews related to healthcare provision supported by IT (e.g.,[6][7][8][9][10]), to the best of the authors' knowledge, systematic reviews of the literature related to the implementation of smart cities are scarce and address specific aspects (e.g., [11][12][13]). Since systematic evidence is required to inform smart city stakeholders and researchers about state of the art solutions, the systematic review reported by the present article aimed to identify the most relevant applications supported by smart city infrastructure with an impact in the provision of healthcare, which is a relevant component of smart living.…”
mentioning
confidence: 99%